Descriptive study on the knowledge, attitudes and practices regarding the diabetic foot - Al-Hariri, Mohammed T. (J Taibah Univ Med Sci, 2017)
OBJECTIVES: The aim of this study is to assess the knowledge, attitudes, practices and risk factors influencing diabetic foot ulcers among diabetes patients attending a diabetic clinic in a Saudi hospital. METHODS: In this cross-sectional study, a random sample of 229 participants was selected from the diabetic clinic of the outpatient department of King Fahd Hospital of the University of Dammam during January to March 2015. A pre-tested structured questionnaire was administered to the diabetes patients to obtain information regarding the outcome variables. RESULTS: The results showed that diabetic foot ulcers were observed among 26% of diabetic patients. Concerning knowledge of the diabetic foot, the majority of participants had good education and favourable attitudes towards diabetic foot care. Interestingly, the results demonstrated that despite these characteristics, a high percentage of the participants ignored very important information and instructions before buying new shoes. CONCLUSION: All diabetic patients with diabetes mellitus should be educated regarding diabetic foot complications and the characteristic specifications of diabetic shoes. However, levels of knowledge, attitudes and practices should be improved. This improvement could be achieved by an awareness programme for the early detection and care of diabetic foot problems in KSA.